Análise técnico-econômica do REVAMP do processos de aquecimento do óleo de palma - Pinheiro, Íkaro Gabriel Cavalcante Monteiro (2017)
A project usually performed in industrial processes is the revamp of production steps, which seeks the inclusion of improvements in the process through adjustments and/or reformulations of a step, or of the whole production process. Thus, after the technical and economic analyses of replacing, for instance, heat exchangers in one step of heating or cooling, one can attest such replacement to be, besides technically, economically feasible and, consequently, it can reduce production costs and increase the profit margin of the final product, making the whole process more cost effective. This paper had as main objective the evaluation of the technical and economical suitability of the substitution of a plate heat exchanger, used in the heating of palm oil, for a shell and tube heat exchanger. To do so, tube and shell heat exchangers were designed to perform the required thermal task; then a heating tank finishes the thermal service, where it achieves temperatures up to 145 to 150° C due to the existence of coils. To enable the quantification of the process temperature, two subsequent steps of oil heating were modelled, the heat exchanger and the tank, and the computer simulation of the model was done, using the Python programming language, through Jupyter Notebook software. Finally, after certifying the replacement proposal was viable both technically and economically, the different types of shell and tube heat exchangers that had been designed were assessed, to decide which one would make it the best investment and were cost worthy; the four criteria for this evaluation (NPV, IRR, PI e Payback period) were based on the initial cost of the designed heat exchanger and its operation reduction cost due to less of saturated steam mass being required to perform the oil heating, were the saturated steam is the heating facility, used both in the heat exchanger as well as in the agitated tank. After the analysis, it was found out that the sixth proposed exchanger features the most economically viable investment, which has an acquisition initial cost of about R$ 196.000,00 and, with it, 2151,65 kg of the steam are saved per thermal batch, providing an annual reduction of $291.347,34.